The interaction between ketone bodies and carbohydrate in human metabolism - Holdsworth, D (2017)
Thesis Abstract: The human brain cannot oxidise fat, so ketone bodies (KBs) are produced in the liver from fat to provide energy in starvation, the brain having a high capacity to oxidise KBs. KB levels rise as insulin falls, with reduced glucose availability, thereby providing a signal to conserve carbohydrate and to switch energy use to fat. Methods: Here, studies were conducted into the relationship between KB and carbohydrate metabolism using exercise and controlled diets to alter substrate availability. A ketone ester (KE) drink was used to raise D-β-hydroxybutyrate (βHB, ±13C-label) levels, at rest and during exercise. Glucose disposal, insulin and other markers of carbohydrate and fat metabolism, KB oxidation and glycogen synthesis rates were investigated by blood sampling, glucose clamp studies, 13C breath analysis and muscle biopsies. Results: βHB oxidation accounted for ≥ 28% of resting VO2, and increased 3-fold with exercise, but was 24% lower when exercising after a low-carb diet. After glycogen-depleting exercise, endogenous insulin levels rose two-fold, glucose disposal increased 32% and glycogen synthesis increased 50% during a 2-hour hyperglycaemic (10 mM glucose) clamp following the KE drink. In overnight fasted healthy controls and type-2 diabetic participants (T2DM), KE increased insulin and lowered glucose concentrations vs. control (zero calorie) drink. There was an increase in glucose disposal during euglycaemic (5 mM glucose) clamping in healthy controls, but no difference in T2DM patients. KE lowered circulating free fatty acids and peripheral lipolysis in T2DM patients. Conclusion: βHB can replace glucose as a fuel, increasing glucose disposal and glycogen synthesis, and increase insulin in health and disease. When carbohydrate is low, muscle βHB oxidation is downregulated to spare KBs for the brain, effects directly or indirectly conserving carbohydrate and protecting the brain. This work is the first to show the metabolic effects of an exogenous (dietary) ketone ester in human, particularly on carbohydrate metabolism, and the effect of substrate availability on ketone oxidation.